State of Maine. In Senate, February 1, 1833 ... Report (Document (Maine. Legislature. Senate), 1833)
February 1, 1833 report of the Joint Select Committee on South Carolina and federal difficulties over thee powers conferred to the general government under the Constitution, particularly in regards to tariffs. The subsequent resolutions indicated sympathy for South Carolina, but regarded nullification of the federal tariffs to be unsound and dangerous. Also includes minority report of committee.